New curriculum guidelines for teacher formation and how they relate to teaching work - Brito, Lúcia Helena de; Nascimento, Natália Cíndia Alves do; Silva, Sirneto Vicente da (Debates em Educação, 2026)
School education and training for work are interrelated and, in contemporary times, the school has become a mediator in the socialization of values necessary for the reproduction of capital. Supported by this understanding, the object of reflection presented in this article is located within the scope of the “National Curricular Guidelines for Initial Training at Higher Level of Teaching Professionals for Basic School Education (DCNs) - CNE/CP No. 4/2024”. Our aim is to understand the implementation of the DCNs in teacher training at higher education level, understanding them as the result of human action, based on the premise of work as the founding category of social being. To this end, methodologically, this research is based on historical-dialectical materialism and uses bibliographical research as techniques, supported by the studies of Marx (2004); Mészáros (2008); Tonet (2006); Lima and Jimenez (2011); Kuenzer (2024), among others, as well as documentary research, covering the main legal frameworks for teacher training at higher education level, with emphasis on CNE/CP Resolution No. 4/2024. The current guidelines deal exclusively with training, disregarding aspects that act directly on the training and work of teachers, such as their appreciation, the job and career plan, working conditions, forms of hiring, as well as continuing education.